Optimal right heart filling pressure in acute respiratory distress syndrome determined by strain echocardiography. Issue 6 (June 2017) - Garcia‐Montilla, Romel; Imam, Faryal; Miao, Mi; Stinson, Kathryn; Khan, Akram; Heitner, Stephen
Abstract : Introduction: Right ventricular (RV) systolic dysfunction is common in acute respiratory distress syndrome (ARDS). While preload optimization is crucial in its management, dynamic fluid responsiveness indices lack reliability, and there is no consensus on target central venous pressure (CVP). We analyzed the utility of RV free wall longitudinal strain (RVFWS) in the estimation of optimal RV filling pressure in ARDS. Methods: A retrospective cross‐sectional analysis of clinical data and echocardiograms of patients with ARDS was performed. Tricuspid annular plane systolic excursion (TAPSE), tricuspid peak systolic velocity (Sʹ), RV fractional area change (RVFAC), RVFWS, CVP, systolic pulmonary artery pressure (SPAP), and left ventricular ejection fraction (LVEF) were measured. Results: Fifty‐one patients with moderate‐severe ARDS were included. There were inverse correlations between CVP and TAPSE, Sʹ, RVFAC, RVFWS, and LVEF. The most significant was with RVFWS ( r :.74, R 2 :.55, P :.00001). Direct correlations with creatinine and lactate were noted. Receiver operating characteristic analysis showed that RVFWS −21% (normal reference value) was associated with CVP: 13 mm Hg (AUC: 0.92, 95% CI: 0.83–1.00). Regression model analysis of CVP, and RVFWS interactions established an RVFWS range from −18% to −24%. RVFWS −24% corresponded to CVP: 11 mm Hg and RVFWS −18% to CVP: 15 mm Hg. Beyond a CVP of 15 mm Hg, biventricular systolic dysfunction rapidly ensues. Conclusions: Our data are the first to show that an RV filling pressure of 13±2 mm Hg—as by CVP—correlates with optimal RV mechanics as evaluated by strain echocardiography in patients with moderate‐severe ARDS.